Oral Tadalafil in Children with Pulmonary Arterial Hypertension - Shiva, A.; Shiran, M.; Rafati, M.; Zamani, H.; Babazadeh, K.; Saeedi, M.; Ala, S. (Drug Research, 2016)
Objective: Tadalafil is a selective Phosphodiesterase-5 inhibitor that has been reported to have vasodilatory and antiproliferative effects on the pulmonary artery. In this study we evaluated the safety and efficacy of oral tadalafil in children with pulmonary arterial hypertension (PAH).Methods: This open label study, prospective and interventional was carried out in 25 known patients aged 2 month–5 years in 3 medical centers in Iran, between March 2013–Jun 2014. Tadalafil suspension was administrated at 1 mg/kg daily for all patients. Hemodynamic and safety parameters were assessed at baseline and then monthly for a total of 4 visits.Results: 19 patients received tadalafil as initial therapy, in all visits significant improvements in mean pulmonary arterial pressure were observed (p<0.01). Of the 25 patients, 6 (24%) had been on sildenafil for longer than 6 months. After transition from sildenafil to tadalafil clinical improvement was noted (p<0.05). Administration of tadalafil suspension was generally safe and well tolerated. Nausea was the most frequently reported adverse events which occurred in 3 patients during treatment.Conclusions: Oral tadalafil was administered easily and tolerated well and improved mean pulmonary artery pressure (MPAP) in children with PAH, which suggests that oral tadalafil may be more effective and safer than sildenafil in the treatment of PAH.
Keywords: children; pulmonary arterial hypertension; phosphodiesterase type 5 (PDE-5) inhibitor; tadalafil